Human Health Risk from Microplastic Contamination in Indonesian Waters Viewed from Distribution, Ecotoxicological Effects and Mitigation Strategies - Fika Wulandari; Neneng Hasanah; Fingky Anjelita Novriani (Journal of Marine and Coastal Science, 2026)
The global plastic pollution crisis has reached alarming levels, with massive annual production and low effective recycling rates. Indonesia is a major contributor of plastic waste to the ocean and the country with the highest microplastics per capita in the world. This study analyzes the distribution of microplastics in Indonesian waters and their risks to human health through the food chain. This study used a literature review method with a narrative review approach on 42 reputable articles. The results show that microplastic contamination is dominated by fragments and fibers from food packaging polymers. Bioaccumulation was confirmed in all fish samples from several waters, accompanied by damage to Deoxyribonucleic Acid (DNA) and histopathology of vital organs, as well as the role of microplastics as heavy metal vectors in consumable biota. The human health risk reaches an emergency level with particle internalization in blood, brain tissue, and breast milk associated with decreased cognitive function. These findings confirm microplastics as contaminants that transfer toxins through the food chain and penetrate biological barriers. Risk-based regulations, equitable distribution of waste management infrastructure, and policies to reduce single-use plastics are needed to protect public health.